Exploring the Relationship Among Teacher Emotional Intelligence, Work Engagement, Teacher Self-Efficacy, and Student Academic Achievement: A Moderated Mediation Model - Wang, Li (Frontiers in Psychology, 2022)
In recent years, many studies have been done to identify the factors that affect teacher emotions at schools. However, the empirical evidence on how teachers’ emotions influence students’ outcomes and performance is not extensive. Against this background, this study explored the correlation between teacher EI and student academic achievement and possible mechanisms may lie in this relationship. A sample of 365 Chinese teachers from 25 public middle schools participated in this study by completing measurements of teacher EI, teacher work engagement, and teacher self-efficacy. The student academic achievement was assessed by the grades of the previous term (February to June 2020) reported by the students. The results indicated that teacher work engagement partially mediated the path from teacher EI and student academic achievement. Moderated mediation further showed that teachers with high self-efficacy had a more significant positive impact on the relationship between teacher work engagement and student academic achievement than teachers with low self-efficacy. The limitations of this study were also discussed.